1991
DOI: 10.1093/oxfordjournals.aje.a115874
|View full text |Cite
|
Sign up to set email alerts
|

Age Distribution of Patients with Medically-Attended Illnesses Caused by Sequential Variants of Influenza A/H1N1: Comparison to Age-Specific Infection Rates, 1978–1989

Abstract: Since influenza A/H1N1 viruses reappeared during the 1977-1978 season, this subtype has contributed 27% of 6,609 documented influenza infections of persons with acute respiratory disease presenting to clinics serving as surveillance sites of the Influenza Research Center in Houston for the 12-year period ending June 1989. Wide differences in the distribution of H1N1 viruses occurred by age group: more than 50% of H1N1 infections were detected among persons aged 10-34 years, compared with 28% for influenza A/H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
51
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 0 publications
17
51
0
4
Order By: Relevance
“…Significance: *P < 0·05, **P < 0·01, ***P < 0·001. The important immune responses to older A(H1N1) strains shown in our study, have also been well demonstrated in another longitudinal study [26], and may be due to boosting by continued exposure to influenza viruses [5,11]. Observation of higher serological titres to earlier strains may also be due to a diminished immune response with each subsequent infection [7].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Significance: *P < 0·05, **P < 0·01, ***P < 0·001. The important immune responses to older A(H1N1) strains shown in our study, have also been well demonstrated in another longitudinal study [26], and may be due to boosting by continued exposure to influenza viruses [5,11]. Observation of higher serological titres to earlier strains may also be due to a diminished immune response with each subsequent infection [7].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, influenza infections may be poorly documented, or go undiagnosed [18]. Using age as a proxy for exposure, studies have identified age-related differences in susceptibility to influenza [9][10][11][12] and this was further underscored during the 2009 A(H1N1) pandemic [19,20]. Not surprisingly, our study identified significant differences in GMT according to birth cohort group.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Further examination of age‐specific rates showed that while the incidence of ILI was high in all pediatric age groups, the incidence of influenza infection was highest among patients aged 2–4 and 5–17 years. Historically in studies with laboratory confirmation, children aged <4 years have had lower influenza incidence than school‐aged children; 4 , 16 , 23 , 24 , 25 however, we found that the incidence in children 2–4 years was higher than in those aged <2 years and more similar to those of school age; perhaps reflecting a greater opportunity for transmission within day care or preschool and more frequent social mixing in this age group.…”
Section: Discussionmentioning
confidence: 52%
“…The role of children in the spread of these viruses is clear, having also been reported in more recent epidemiological studies. [18][19][20][21] Children do not only disseminate the influenza virus, but can also present significant morbidity associated with flu infections, with less typical and sometimes more severe clinical manifestations. 22 Encephalitis cases caused by the influenza virus have been described in children.…”
Section: Impact Of the Influenza Virus On Childrenmentioning
confidence: 99%